Trends in skin fungal infection in Tripoli, Libya, during 2007–2015 - Atia, Ahmed; Ashour, Abdulsalam; Elyounsi, Najla (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
Background: Skin infection is common worldwide and continues to rise. This study was undertaken to determine the trends in skin fungal infection in patients attending a tertiary hospital. Methods: A total of 253 patients, suspected of superficial and cutaneous skin infections, referred to the Medical Mycology Laboratory of Berustta-Milad Hospital, Libya, were included from attendees over the past 8 years (January 2007–December 2015). Specimens were attained from clinically atypical skin lesions, hair or nail samples of infected patients through scraping. Dermatophyte isolates were identified by studying macroscopic and microscopic characteristics of their colonies. Results: Of 253 samples, fungi were detected in 179 (70.8%) by potassium hydroxide, of which 70 (39.1%) samples were Aspergillus infection followed by 55 (30.7%) samples which were culture positive of Trichophyton spp., 33 (18.4%) samples were isolates of Candida, and 21 (11.8%) due to other opportunistic fungi. Patients with the age group of 17–28 years were more affected. Conclusion: Skin fungal infections are common there is a need to increase the awareness of risk factors contributing to skin fungal infections. Further larger and more detailed epidemiological studies of fungus-induced dermatophytosis which have public health implication are needed.
Keywords: Dermatophytic; infection; mycosis; skin